About lithium and lithium in Serbia - Simonović, Branislav (Napredak, 2024)
This paper summarizes basic information about lithium, its physical and chemical characteristics and its occurrence in different minerals, especially in jadarite. A review of different types of application of lithium and their compounds in different industries, especially in medicine, is presented here. Also, the review of literature data on lithium occurrence in water and various food and its influence on humans is described. The role of lithium in warfare is also mentioned. Detailed data on different types of lithium batteries, including the new type of lithium batteries with solid electrolyte is given. Data on lithium production and lithium demand, including the increase of lithium demand in the near future is summarized in this article. In the part related to the Serbian Jadar project, some basic data on this project is given; that includes the technological procedure of lithium production, solid and liquid waste and landfill for waste deposition, especially in regard to the environmental protection. The part of beginning with the subtitle “Shouting and shame about lithium in Serbia” contains critical review on numerous nonsensical claims, misinformation and lies about lithium and Jadar project, especially about sulphuric acid and lithium toxicity that were spread across Serbia in the past four years, becoming an object of intimidation of Serbian citizens. Aiming to show how nonsensical and false these claims are, the data from valid and credible verifiable sources were cited. The final part of the text contains proposals about things that should be done in relation to the Jadar project.